Perkembangan Urban Sprawl Kota Makassar Tahun 2008-2018 - Putri Nurul Hakiki; Ananto Yudoyono; Arifuddin Akil (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
The more complex and large role of a city will affect the rate of population growth. This occurs in Makassar City, which is one of the largest cities in Eastern Indonesia with a population growth rate of 1.32% in 2017 which is impact to the shifting of urban functions towards the outskirts and the tendency to occur in urban sprawl in Biringkanaya District Makassar City. This study using spatial analysis and soring analysis, to find out the significant variables using multiple linear regression analysis and to determine the direction carried out by SWOT and AHP techniques. The results of the analysis show that 1) the classification of urban sprawl characteristics in Biringkanaya District is divided into 4 typologies; 2) variable population density, building density, distance from the city center, development within the range of road networks and the pattern of frog jumping simultaneously influencing the development of urban sprawl in Biringkanaya District, Makassar City with a 95% determination rate. 3). The strategy in eliminating the development of urban sprawl in Biringkanaya District, Makassar City can be done through community service planning, intermodal transportation provision, opportunities for investors to collaborate and control to control building construction in a compact manner.